A WORKSHOP ON UTILIZING NEARPOD: SOLUTION FOR HYBRID HOME-BASED LEARNING IN THE NEW NORMAL - Paulina Erawati Paramita; Dudy Effendy (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
This article provides an overview of the workshop on "Utilizing Nearpod for Hybrid Home-Based Learning in the New Normal" organized by Bimbel YCI (Yayasan Cinta Indonesia) on 11 December 2021. The workshop was conducted online via Zoom and aimed to provide solutions for educators and administrators on utilizing Nearpod for hybrid home-based learning. It covers the background of the workshop, the method used, and the key takeaways for participants. The workshop began with an overview of the current situation of hybrid home-based learning in the new normal, followed by an introduction to the Nearpod platform and its features. Participants then learned how to create a Nearpod account and navigate the platform, create and manage classes, monitor student progress, provide feedback and engage students through interactive activities, as well as how to use Nearpod's built-in assessment tools. The workshop was concluded with a Q&A session for further questions and clarification, and a summary of key points covered in the workshop was provided along with additional resources and support for continued learning.